Practical Scala for Java developers from pattern matching and testing to functional programming and concurrency - Evans, Benjamin J. (O'Reilly Media, 2016)
"You're a Java developer who has heard of Scala and maybe now you're being asked to work on Scala code. Concerned? Don't be. Taught by Java-Scala experts Ben Evans and Julian Templeman, this courseanswers the questions you want answered: What is Scala really useful for? Does it help with concurrency? What is functional programming and how much do I really need to know? How do I set up a Scala development environment, how do I test, and what are the must-know Scala idioms? If you're an intermediate level Java developer with six months of experience under your belt, then this course will quickly transform you from the Scala ignorant to the Scala capable."--Resource description page.